1999
DOI: 10.1038/sj.bmt.1701576
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of chemotherapy-purged PBSC collections from high-risk leukemia patients: a pilot study

Abstract: We have recently demonstrated that the combination of the alkylating agent nitrogen mustard (NM) and etoposide (VP-16) is capable of eliminating, ex vivo, leukemic cells contaminating PBSC collections and this is associated with a significant recovery of primitive and committed hematopoietic progenitor cells. Based on these data a pilot study on autologous transplantation of NM/VP-16 purged PBSC for high-risk leukemic patients was recently initiated. Twelve patients (seven females and five males) with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…6,20 Progenitor cell apheresis was begun after an absolute count of 10 CD34 + cells/ l was achieved during the recovery phase after consolidation therapy. As already reported, 17,18,21 circulating stem cells were collected by using either a Fenwal CS3000 continuous flow blood cell separator (Baxter, Rome, Italy) or a Cobe Spectra separator (Cobe BCT, Lakewood, CO, USA) to obtain a minimum yield of 2 × 10 6 CD34 + cells/kg. Non-mobilizing patients underwent bone marrow harvest, as previously reported.…”
Section: Bone Marrow Collection Leukapheresis Procedures and Pbsc Prmentioning
confidence: 99%
See 2 more Smart Citations
“…6,20 Progenitor cell apheresis was begun after an absolute count of 10 CD34 + cells/ l was achieved during the recovery phase after consolidation therapy. As already reported, 17,18,21 circulating stem cells were collected by using either a Fenwal CS3000 continuous flow blood cell separator (Baxter, Rome, Italy) or a Cobe Spectra separator (Cobe BCT, Lakewood, CO, USA) to obtain a minimum yield of 2 × 10 6 CD34 + cells/kg. Non-mobilizing patients underwent bone marrow harvest, as previously reported.…”
Section: Bone Marrow Collection Leukapheresis Procedures and Pbsc Prmentioning
confidence: 99%
“…From May 1994, all patients received G-CSF (10 g/kg/day), to mobilize peripheral blood progenitor cells. 17,18 When mobilization was insufficient (Ͻ10 CD34 + cells/ l), bone marrow was subsequently harvested in steady-state conditions.…”
Section: Single Novia Consolidation Therapy Group (Figure 1a)mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative advantages and disadvantages of autologous bone marrow transplantation (ABMT) or peripheral blood stem cell (PBSC) transplantation are still under evaluation. PBSC transplantation performed after standard induction regimens appears superior to ABMT as regards the recovery times of polymorphonuclear and platelet counts (Korbling et al , 1991; To et al , 1992; Sanz et al , 1993; Demirer et al , 1996; Schiller et al , 1997; Reiffers et al , 1992), but concerns have been raised regarding an increased potential for relapse following the procedure (Korbling et al , 1991; Sanz et al , 1993; Laporte et al , 1997; Mehta et al , 1995; Motta et al , 1997; Lemoli et al , 1999). Thus, intensification of induction/consolidation chemotherapy has been proposed in order to determine in vivo purging prior to PBSC (Mehta et al , 1995).…”
mentioning
confidence: 99%
“…46,47 Different physical, clinical, and immunologic means have been used to purge the contaminating tumor cells ex vivo, including the use of activated autologous NK cells to overcome relapse. [48][49][50][51][52] In our previous report investigating the possibility of syngeneic NK cells as purging agents in a murine leukemia model, we demonstrated that blocking inhibitory receptors specific for class I on a subset of syngeneic NK cells during ex vivo purging of C1498 murine leukemia contaminating the bone marrow graft significantly increased the extent of tumor cell elimination by syngeneic NK cells. 53 We also demonstrated that transplanting tumorcontaminating BMCs purged with syngeneic NK cells with inhibitory receptor blockade resulted in an increased proportion of long-term survivors without affecting hematopoietic cell recovery.…”
mentioning
confidence: 99%